A Business Model of Luxury Brands and Contemporary Art: A Case Study of Art Mall in China. Issue 2 (4th May 2021) - Shih, WenYing Claire
Abstract : ABSTRACTLuxury brands following years of diversification have recently discovered that contemporary art represents their interests by associating art with luxury artifacts. This attaches intangible values to mundane products by shrouding them with art in the artification process. Contemporary art, on the other hand, has become more of a business network operating within the rules of the market economy. It has become a common practice for luxury brands to collaborate with contemporary artists by staging exhibitions of contemporary art in their purpose-built exhibition halls that serve as inspiration for their creative directors to develop merchandise ranges. In China, a novel retail concept of the art malls has emerged. Private art patrons, developers, state authorities and luxury brands have entered into partnerships. Luxury brands eager to tap into the lucrative markets of Chinese cities, have discovered that art malls best serve their purposes as experiential retailing takes center stage. The partnering actors in both luxury brands and Chinese art mall developers have managed to institute a remarkable business model in the form of a transcontinental network. By capturing value, network participants have generated network capital, which has led them to sources of competitive advantage. In this arrangement, Aesthetic Capitalism has prevailed where the orchestration of excitement takes center stage thus, circumventing the purer intentions of the Creative Economy promulgated by the United Nations.